Impact of the COVID-19 Pandemic on Mental Health in People Living with HIV/AIDS: A Literature Review - Indriani, Ria; Setyawati, Anita (Multidiscience : Journal of Multidisciplinary Science, 2025)
The COVID-19 pandemic has profoundly affected global mental health, with people living with HIV/AIDS (PLHIV) particularly vulnerable due to their pre-existing challenges and heightened susceptibility to psychological impacts. This study reviews the literature to analyze the mental health implications of the pandemic on PLHIV, focusing on outcomes during and after the pandemic. A systematic review of ten studies retrieved from PubMed, CINAHL, and Google Scholar reveals that PLHIV experiences elevated risks of anxiety, depression, social isolation, and psychological trauma. These conditions are exacerbated by stigma, disrupted healthcare services, and pandemic-induced stressors such as fear of infection and economic pressures. The review also highlights the complex interplay between HIV/AIDS, mental health, and the pandemic, with evidence showing that psychosocial stress can impair immune function, cognitive abilities, and adherence to antiretroviral therapy (ART). The methodological analysis of the selected studies underscores the significance of robust psychosocial support in mitigating mental health challenges and improving disease prognosis. Comprehensive interventions, including stigma reduction strategies, enhanced access to mental health services, and public education, are critical to addressing these compounded vulnerabilities. The findings emphasize the necessity of integrating mental health care into holistic healthcare frameworks for PLHIV, especially in the post-pandemic era.